Effects of pulsatile shear stress on circulating tumor cells. - Hom, William Warren. (2013)
Metastasis has been observed to be an inefficient process but the factors that prevent most malignant cancer cells from successfully forming secondary tumors are not fully understood. The main way in which cancer cells spread to distant parts of the body is through the vascular system. Fluid shear stress is one of the major physical forces exerted on CTCs (circulating tumor cells) while traveling through the bloodstream but its effects on cancer cell survivability has received little attention. This study utilizes a continuous, pulsatile flow system to study the effects of fluid shear stress on CTC survival over a prolonged period of time. Two types of human breast cancer cells which were transfected with a caspase-3 based FRET (fluorescence resonance energy transfer) biosensor to detect apoptosis were used: highly invasive MDA-MB-231-C3 and minimally invasive MCF-7-C3. The cells were exposed to two levels of fluid shear stress (5 and 15 dyn cm-2) for 48 hours and the percentage of apoptotic cells were measured at 12, 18, 24, 36, and 48 hours. This study shows that highly invasive cancer cells have a higher resistance to shear stress induced apoptosis than the less invasive cancer cells.